Injectable collagen microspheres and preparation method and application thereof

Preparation of injectable collagen microspheres by using polymer-loaded collagen formed by sodium hyaluronate and chitosan solves the problems of short maintenance time of existing fillers and stimulating excessive inflammation, achieving collagen regeneration and good biocompatibility.

CN119770741APending Publication Date: 2025-04-08YAU BIOTECHNOLOGY (SHANGHAI) CO LTD

Patent Information

Application Number
CN202510071610.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing facial fillers have problems such as short filling and maintenance time, stimulating excessive inflammatory responses and poor cell affinity, which makes it difficult to effectively promote collagen regeneration.

Method used

Injectable collagen microspheres are prepared by loading collagen with a polymer formed by sodium hyaluronate and chitosan through amide bonds. The microspheres have three-dimensional mesh structure and gradient degradation characteristics.

Benefits of technology

The good biocompatibility and porous structure of collagen microspheres in the body are achieved, which is conducive to cell adhesion and deposition of neoproteins, continuously stimulate collagen regeneration, and avoid severe inflammatory reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770741A_ABST
    Figure CN119770741A_ABST
Patent Text Reader

Abstract

The present application provides an injectable collagen microsphere and a preparation method and application thereof, the preparation method comprising the following steps: S1: preparing a polymer, the polymer comprising sodium hyaluronate and chitosan; S2: adding the polymer and a neutralization solution to a collagen solution to obtain a mixed solution; S3: heating and stirring the mixed solution to obtain collagen microspheres; S4: drying the collagen microspheres. The injectable collagen microspheres prepared by the preparation method have a three-dimensional mesh structure; they have good biocompatibility when used as facial fillers and can promote collagen regeneration; at the same time, because collagen and the polymer are not cross-linked, when implanted into the human body, collagen is degraded first, and the polymer is degraded within 6 to 12 months. The overall gradient degradation of the material is conducive to the continuous stimulation of collagen regeneration in the body and avoids severe inflammatory reactions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to an injectable collagen microsphere and a preparation method and application thereof. Background Art

[0002] With the improvement of living standards, people's pursuit of beauty is getting higher and higher. Medical beauty filling refers to the shaping method of using fillers to fill local tissues of the human body. It can modify facial features, fill tissue contour depressions and create contour lines, so that the target parts can achieve a full and three-dimensional state. Sodium hyaluronate gel fillers are currently the most widely used type of products, but the filling duration of gel products is relatively short. Absorbable polymer microsphere fillers (polylactic acid, polycaprolactone) can stimulate collagen regeneration while filling, and are increasingly attracting people's attention, such as "baby face needle" and "girl needle" products. This type of product stimulates the body to produce an inflammatory response by subcutaneous injection of microspheres, thereby forming a fibrous capsule composed of collagen to achieve the purpose of facial rejuvenation. Moderate inflammatory response in the process of tissue healing can promote healing and promote collagen proliferation, while excessive inflammatory response may cause pathological scars. The degradation of synthetic polymer materials in the body is not a gradual degradation process from the outside to the inside, but a process of overall hydrolysis of the material. There is a peak period and disintegration period of polymer material degradation, which will stimulate excessive inflammatory response. When registering such products, there will be reminders to pay attention to risks such as nodules, granulomas, and inflammatory reactions. At the same time, the cells on the surface of synthetic polymer materials have poor affinity, which is not conducive to cell adhesion and growth, and is not conducive to tissue regeneration.

[0003] In situ tissue regeneration and its engineered biomaterials have always been a hot topic in the field of regenerative medicine. When implanted into a biomaterial scaffold, a series of serum proteins are adsorbed, changing its surface properties; endogenous immune cells attach to the adsorbed proteins and release cytokines and chemokines; the release of these molecules leads to the recruitment of endogenous progenitor cells and stem cells. After initial attachment, these cells synthesize and deposit new proteins on the biomaterial surface.

[0004] Compared with the simple pro-inflammatory response of absorbable polymer materials to form fibrous capsules, natural biopolysaccharides and collagen polymer materials with better cell affinity are used. When implanted in the body, they show higher cell infiltration, angiogenesis and collagen-rich ECM deposition, and transition from simple inflammatory-stimulated hyperplasia to in situ tissue regeneration.

[0005] Sodium hyaluronate molecules contain carboxyl groups, and chitosan contains amino groups. Under the action of a dehydrating agent, dehydration can occur to form amide bonds. Patent CN 113663126 A uses this principle to prepare sodium hyaluronate gel microspheres using chitosan as a cross-linking agent, but gel products can only play a short-term filling role and cannot promote collagen regeneration. Absorbable polymer microsphere fillers have the effect of stimulating collagen regeneration, but this type of material has poor cell affinity and there is a risk of excessive inflammatory response. According to the mechanism of in situ tissue regeneration, the injectable collagen microspheres prepared by the present invention using natural polymer materials are an ideal filling material. Summary of the invention

[0006] In view of the defects and shortcomings of the above-mentioned facial fillers, the present invention has developed a solid injectable collagen microsphere, which is composed of collagen and sodium hyaluronate chitosan polymer, wherein the polymer is obtained by polymerization of sodium hyaluronate and chitosan via amide bond connection. The injectable collagen microsphere has a three-dimensional mesh structure and can be gradiently degraded. It has good biocompatibility when used as a facial filler and promotes collagen regeneration.

[0007] To achieve the above-mentioned purpose, in the first aspect, the present invention provides a method for preparing injectable collagen microspheres, comprising the following steps: S1: preparing a polymer, wherein the polymer comprises sodium hyaluronate and chitosan; S2: adding the polymer and a neutralization solution to a collagen solution to obtain a mixed solution; S3: heating and stirring the mixed solution to obtain collagen microspheres; S4: drying the collagen microspheres. The beneficial effect is that the preparation method provided by the present invention first prepares sodium hyaluronate and chitosan polymers, and then loads collagen on the polymer, and the collagen in the injectable collagen microspheres prepared thereby does not cross-link with the polymer, and will be degraded first after being implanted into the human body, and the slow degradation of the polymer can stimulate the regeneration of collagen in the body.

[0008] In some embodiments, S1 includes: S11: preparing a first mixed solution, the first mixed solution including a sodium hyaluronate solution and a chitosan solution; S12: emulsifying the first mixed solution to obtain an emulsified solution; S13: solidifying the emulsified solution to form a microcarrier; S14: treating the microcarrier to cause a cross-linking reaction to form a polymer; S15: cleaning and drying the polymer. The beneficial effects are: sodium hyaluronate is an important component of the human body; chitosan is a biological material extracted from shrimp and crab shells. Sodium hyaluronate and chitosan are used as raw materials, and the microcarrier prepared thereby is absorbable and degradable, with a degradation time of 6 to 12 months, and has good biocompatibility.

[0009] In some embodiments, in S2: the collagen solution is obtained by dissolving collagen in a hydrochloric acid solution, the collagen concentration is 3 mg / ml~15 mg / ml, and the hydrochloric acid concentration in the hydrochloric acid solution is 0.01 mol / L.

[0010] In some embodiments, in S2: the ionic strength of the neutralization solution is 0.03-0.1, the neutralization solution is a solution of sodium hydroxide and sodium dihydrogen phosphate; and the pH value of the mixed solution is 6-8.

[0011] In some embodiments, S3 includes: heating the temperature of the mixed solution from 1°C~15°C to 15°C~30°C, the heating rate is 1°C / h~10°C / h, and continuously stirring the mixed solution during the heating process, the stirring rate is 100rpm~500rpm, and the stirring time is 5h~16h.

[0012] In some embodiments, the S11 includes: S111: dissolving sodium hyaluronate in a monovalent metal salt solution to obtain the sodium hyaluronate solution; S112: dissolving chitosan in a monovalent metal salt acetic acid solution to obtain the chitosan solution; S113: mixing the sodium hyaluronate solution and the chitosan solution to obtain the first mixed solution. Its beneficial effect is that since each unit in the chitosan molecule contains a positive charge and every two units of sodium hyaluronate contain a negative charge, due to the excessively high charge density, it is easy for the materials to be mutually coated and stacked, and it is difficult to achieve orderly combination of materials and a high cross-linking density. In order to achieve a high degree of cross-linking and a stable charge state of the microcarrier, sodium hyaluronate and chitosan are dissolved in a metal salt solution, and the electrostatic interaction between the two is removed by the electrostatic coagulation agent metal salt ions, and the mixture is mixed into a uniform solution, rather than electrostatically combining to form a precipitate.

[0013] In some embodiments, the step S12 includes: S121: adding an oil phase and an emulsifier into a container and mixing; S122: adding the first mixed solution into the container and stirring and emulsifying to obtain the emulsified solution. The beneficial effect is that the solution is prepared into droplets of a certain particle size by an emulsification method.

[0014] In some embodiments, the S13 comprises: S131: adding a first hydrophilic organic solvent to the emulsified solution to solidify and form microcarriers; S132: leaching out the microcarriers. The beneficial effect is that the first hydrophilic organic solvent is used to wash away the electrostatic polymerizer metal salt ions in the droplets, the chitosan sodium hyaluronate is subjected to in-situ orderly electrostatic polymerization, and solid microcarriers are formed, and the microcarriers are leached out from the emulsified solution.

[0015] In some embodiments, the S14 includes: S141: adding a catalyst to a second hydrophilic organic solvent; S142: adding the carrier to the second hydrophilic organic solvent for a cross-linking reaction to generate the polymer. The beneficial effect is that the electrostatic polymerization in the solid microcarrier is an unstable structure, and the catalyst can remove a water molecule in the electrostatic binding part to form a stable chemical bond amide bond, and finally achieve a cross-linking degree of the polymer greater than 50%.

[0016] In some embodiments, the step S15 includes: S151: washing the polymer with a third hydrophilic organic solvent; S52: drying the washed polymer. The beneficial effect is that the third hydrophilic organic solvent is used to wash and remove the attached impurities on the polymer.

[0017] In some embodiments, the concentration of the monovalent metal salt in the monovalent metal salt solution is 0.5-2 mol / L, the mass percentage of acetic acid in the monovalent metal salt acetic acid solution is 0.5-3%; the concentration of the sodium hyaluronate solution is 0.5%-10%, and the concentration of the chitosan solution is 0.5%-10%.

[0018] In some embodiments, the monovalent metal salt includes at least one of sodium chloride and potassium chloride.

[0019] In some embodiments, the oil phase includes at least one of liquid paraffin, mineral oil and vegetable oil; and the emulsifier includes at least one of sorbitan monooleate polyoxyethylene ether and sorbitan oleate.

[0020] In some embodiments, the mass ratio of the oil phase to the emulsifier is (35~45):1; the mass ratio of the oil phase to the first mixed solution is 1:(4~10); the stirring rate of the emulsification is 500rpm~2000rpm, and the stirring time of the emulsification is 2h~8h.

[0021] In some embodiments, the first hydrophilic organic solvent, the second hydrophilic organic solvent, the third hydrophilic organic solvent and the fourth hydrophilic organic solvent all include at least one of ethanol, acetone and dimethylformamide; the first hydrophilic organic solvent, the second hydrophilic organic solvent and the third hydrophilic organic solvent are all aqueous solutions with a concentration of 30% to 95%.

[0022] In some embodiments, the volume ratio of the first hydrophilic organic solvent to the oil phase is (0.8~1.2):1; the addition rate of the first hydrophilic organic solvent is 10ml / min~100ml / min, and stirring is continued during the addition of the first hydrophilic organic solvent, the stirring rate is 100rpm~800rpm, and the stirring time is 1h~15h.

[0023] In some embodiments, the mass ratio of the second hydrophilic organic solvent to the carrier is (10-50):1; the number of washing times is 1-5 times, and the time for each washing is 1-4 hours.

[0024] In some embodiments, the catalyst includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysulfosuccinimide (NHS), and the concentration of the catalyst is 0.5‰~4‰.

[0025] In some embodiments, the temperature of the cross-linking reaction is 10° C. to 50° C., and the time of the cross-linking reaction is 5 h to 24 h.

[0026] In a second aspect, an embodiment of the present invention provides an injectable collagen microsphere, comprising collagen, sodium hyaluronate and chitosan, wherein the sodium hyaluronate and the chitosan are connected by amide bonds to form a polymer; the mass ratio of the collagen to the injectable collagen microsphere is 10-50%, and the ratio of the sodium hyaluronate to the chitosan is (1.5-2.5):1.

[0027] In some embodiments, the diameter of the injectable collagen microspheres is 10µm to 800µm, and the injectable collagen microspheres have a three-dimensional mesh structure.

[0028] In a third aspect, an embodiment of the present invention provides a use of injectable collagen microspheres as an implant filler, which can promote the regeneration of collagen in human tissue.

[0029] The beneficial effects of the present invention are that the injectable collagen microspheres prepared by the method of the present invention have the following advantages: 1. Collagen loaded on sodium hyaluronate and chitosan polymers has better biocompatibility. At the same time, the injectable collagen microspheres have a porous structure, which is conducive to the adhesion of endogenous progenitor cells in the body and promotes the synthesis and deposition of new proteins on the surface of the material.

[0030] 2. After the prepared injectable collagen microspheres are implanted in the body, they will gradually degrade first because the human body contains proteases and the collagen has not been cross-linked. Since the polymer has a high degree of cross-linking, it degrades more slowly. The degradation time of injectable collagen microspheres is 6-12 months. The gradual degradation of the material is conducive to the continuous stimulation of collagen regeneration in the body and avoids severe inflammatory reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the structure of injectable collagen microspheres according to an embodiment of the present invention; Figure 2This is a diagram of the three-dimensional mesh structure of injectable collagen microspheres according to an embodiment of the present invention; Figure 3 This is a flow chart of a method for preparing injectable collagen microspheres according to an embodiment of the present invention; Figure 4 This is an infrared spectrum of the microcarriers in the injectable collagen microspheres according to an embodiment of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the usual meanings understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Unless otherwise specified, the "connection" described in this article can be a direct connection or an indirect connection, that is, connected through an intermediate.

[0033] In view of the problems existing in the prior art, the embodiments of the present invention provide a method for preparing injectable collagen microspheres. Figure 3 , comprising the following steps: S1: preparing a polymer, wherein the polymer comprises sodium hyaluronate and chitosan; S2: adding the polymer and a neutralization solution to a collagen solution to obtain a mixed solution; S3: heating and stirring the mixed solution to obtain collagen microspheres; S4: drying the collagen microspheres.

[0034] In this embodiment, the sodium hyaluronate (HA) is an important component of the human body and is an acidic polysaccharide with a negative charge; the chitosan (CS) is a biological material extracted from shrimp and crab shells and is an alkaline polysaccharide with a positive charge. The sodium hyaluronate and the chitosan are cross-linked to form a polymer, and the collagen is precipitated from the solution and loaded on the polymer to obtain injectable collagen microspheres.

[0035] In some embodiments, S1 includes: S11: preparing a first mixed solution, the first mixed solution including a sodium hyaluronate solution and a chitosan solution; S12: emulsifying the first mixed solution to obtain an emulsified solution; S13: solidifying the emulsified solution to form a microcarrier; S14: treating the microcarrier to cause a cross-linking reaction to form a polymer; S15: cleaning and drying the polymer.

[0036] In some embodiments, in S2: the collagen solution is obtained by dissolving collagen in a hydrochloric acid solution, the collagen concentration is 3 mg / ml~15 mg / ml, and the hydrochloric acid concentration in the hydrochloric acid solution is 0.01 mol / L.

[0037] In this embodiment, the collagen can be obtained by enzymatic hydrolysis of animal tendons or dermis under acidic conditions.

[0038] In some embodiments, in S2: the ionic strength of the neutralization solution is 0.03-0.1, the neutralization solution is a solution of sodium hydroxide and sodium dihydrogen phosphate; and the pH value of the mixed solution is 6-8.

[0039] In some embodiments, S3 includes: raising the temperature of the mixed solution from 1°C~15°C to 15°C~30°C, the heating rate is 1°C / h~10°C / h, and continuously stirring the mixed solution during the heating process, the stirring rate is 100rpm~500rpm, and the stirring time is 5h~16h.

[0040] In this embodiment, collagen is precipitated by stirring. In this process, the collagen is precipitated using the polymer microcarrier as a template. Specifically, collagen tends to grow with the charges carried by the amino and carboxyl groups in the polymer molecules as the nucleus and precipitate using the polymer microcarrier as a template.

[0041] In some embodiments, the S11 includes: S111: dissolving sodium hyaluronate in a monovalent metal salt solution to obtain the sodium hyaluronate solution; S112: dissolving chitosan in a monovalent metal salt acetic acid solution to obtain the chitosan solution; S113: mixing the sodium hyaluronate solution and the chitosan solution to obtain the first mixed solution.

[0042] In some embodiments, the S12 includes: S121: adding the oil phase and the emulsifier into a container and mixing; S122: adding the first mixed solution into the container and stirring and emulsifying to obtain the emulsified solution.

[0043] In some embodiments, the S13 comprises: S131: adding a first hydrophilic organic solvent to the emulsified solution to solidify and form microcarriers; S132: leaching out the microcarriers.

[0044] In this embodiment, a first hydrophilic organic solvent is added to the emulsified solution to solidify the emulsified solution to form the microcarriers. The emulsified solution is not solidified as a whole, but solidified to form a plurality of microcarriers. At this time, there is unsolidified emulsified solution and solidified microcarriers in the container. The microcarriers can be leached out using a filtration device. At this time, the solidified microcarriers are the chitosan and the sodium hyaluronate bonded together by electrostatics, and are not stable structures. They will depolymerize under hypertonic conditions or alkaline conditions (chitosan is not positively charged under alkaline conditions).

[0045] In some embodiments, the S14 includes: S141: adding a catalyst to a second hydrophilic organic solvent; S142: adding the carrier to the second hydrophilic organic solvent to perform a cross-linking reaction to generate the polymer.

[0046] In this embodiment, the cross-linking reaction of the microcarrier refers to removing a water molecule from the electrostatic binding part of chitosan and sodium hyaluronate to form a stable chemical bond amide bond, and finally achieving a cross-linking degree greater than 50%. Figure 4 From the infrared spectrum, we can see that the cross-linked sodium hyaluronate chitosan polymer has a wavelength of 1650cm -1 and 1559cm -1 A new amide bond peak is formed at the wavelength.

[0047] In some embodiments, the S15 includes: S151: washing the polymer with a third hydrophilic organic solvent; S52: drying the washed polymer.

[0048] In some embodiments, the concentration of the monovalent metal salt in the monovalent metal salt solution is 0.5-2 mol / L, the mass percentage of acetic acid in the monovalent metal salt acetic acid solution is 0.5-3%; the concentration of the sodium hyaluronate solution is 0.5%-10%, and the concentration of the chitosan solution is 0.5%-10%.

[0049] In some embodiments, the monovalent metal salt includes at least one of sodium chloride and potassium chloride.

[0050] In this embodiment, other metal salts that can play the same role can also be used as electrostatic coagulation agents to allow the sodium hyaluronate solution and the chitosan solution to be evenly mixed rather than electrostatically combining to form precipitation.

[0051] In some embodiments, the oil phase includes at least one of liquid paraffin, mineral oil and vegetable oil; and the emulsifier includes at least one of sorbitan monooleate polyoxyethylene ether and sorbitan oleate.

[0052] In this embodiment, the oil phase refers to an oil-based liquid. In addition to liquid paraffin, mineral oil and vegetable oil, other oil-based liquids can also meet the requirements of this embodiment.

[0053] In some embodiments, the mass ratio of the oil phase to the emulsifier is (35~45):1; the mass ratio of the oil phase to the first mixed solution is 1:(4~10); the stirring rate of the emulsification is 500rpm~2000rpm, and the stirring time of the emulsification is 2h~8h.

[0054] In some embodiments, the first hydrophilic organic solvent, the second hydrophilic organic solvent and the third hydrophilic organic solvent all include at least one of ethanol, acetone and dimethylformamide; the first hydrophilic organic solvent, the second hydrophilic organic solvent and the third hydrophilic organic solvent are all aqueous solutions with a concentration of 30% to 95%.

[0055] In this embodiment, the concentrations of the first hydrophilic organic solvent, the second hydrophilic organic solvent and the third hydrophilic organic solvent may be the same, or the same organic solvent may be used.

[0056] In some embodiments, the volume ratio of the first hydrophilic organic solvent to the oil phase is (0.8~1.2):1; the addition rate of the first hydrophilic organic solvent is 10ml / min~100ml / min, and stirring is continued during the addition of the first hydrophilic organic solvent, the stirring rate is 100rpm~800rpm, and the stirring time is 1h~15h.

[0057] In some embodiments, the mass ratio of the second hydrophilic organic solvent to the carrier is (10-50):1; the number of washing times is 1-5 times, and the time for each washing is 1-4 hours.

[0058] In some embodiments, the catalyst includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysulfosuccinimide (NHS), and the concentration of the catalyst is 0.5‰~4‰.

[0059] In some embodiments, the temperature of the cross-linking reaction is 10° C. to 50° C., and the time of the cross-linking reaction is 5 h to 24 h.

[0060] In a second aspect, an embodiment of the present invention provides an injectable collagen microsphere, comprising collagen, sodium hyaluronate and chitosan, wherein the sodium hyaluronate and the chitosan are connected by amide bonds to form a polymer; the mass ratio of the collagen to the injectable collagen microsphere is 10-50%, and the ratio of the sodium hyaluronate to the chitosan is (1.5-2.5):1.

[0061] In some embodiments, reference Figure 1 and Figure 2 The diameter of the injectable collagen microspheres is 10µm to 800µm, and the injectable collagen microspheres have a three-dimensional mesh structure.

[0062] In a third aspect, an embodiment of the present invention provides a use of injectable collagen microspheres as an implant filler, which can promote the regeneration of collagen in human tissue.

[0063] The present invention is further described below by specific examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be obtained commercially, and the reagents and materials involved can also be synthesized by conventional synthesis methods.

[0064] Example 1 1) Dissolve sodium hyaluronate in 1 mol / L sodium chloride solution to a concentration of 1%; dissolve chitosan in 1 mol / L sodium chloride 1% acetic acid solution to a chitosan solution concentration of 5%. Mix the two solutions, with the mass ratio of sodium hyaluronate to chitosan being 2:1.

[0065] 2) Add 2% sorbitan oleate to liquid paraffin, then add the mixed solution to stir and emulsify, the mass ratio of the mixed solution to the oil phase is 1:6, the emulsification stirring rate is 1500 rpm, and the emulsification stirring time is 8 hours.

[0066] 3) The stirring speed was adjusted to 100 rpm. During the stirring process, a hydrophilic organic solvent (ethanol) with an equal volume to the oil phase was added at a concentration of 85%. The solidification time was 5 h, and microspheres were obtained by leaching.

[0067] 4) Dissolve 1‰ of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysulfosuccinimide (NHS) in 85% hydrophilic organic solvent (ethanol) solution, add the cleaned microcarriers thereto, and crosslink at 10°C for 24 hours. The crosslinked microcarriers are washed with 85% hydrophilic organic solvent (ethanol) solution to remove the catalyst, and dried to obtain a polymer.

[0068] 5) Collagen is extracted from animal tendons or dermis by enzymatic hydrolysis under acidic conditions, and the collagen is dissolved in 0.01 mol / L hydrochloric acid solution with a collagen concentration of 3 mg / ml-15 mg / ml. Sodium hyaluronate chitosan polymer is added to the collagen solution.

[0069] 6) Prepare neutralization solution: sodium hydroxide and sodium dihydrogen phosphate solution, with an ionic strength of 0.06. Add the neutralization solution to the collagen solution, and the pH value of the neutralized solution is 7. After adding the neutralization solution, the initial temperature of the solution is 1°C, and the temperature is increased at a rate of 10°C / h to 25°C. The stirring rate is 300 rpm, and the stirring time is 10 hours. Wash the microspheres with purified water and obtain injectable microspheres by freeze drying.

[0070] Among them: the average particle size of the injectable microspheres was observed and measured using a scanning electron microscope, and the injectable microspheres were implanted subcutaneously in rats to observe the degradation time of the microspheres; The surface charge density of the polymer was tested by a particle charge tester, and the infrared spectrum of the polymer was tested by a Fourier transform infrared spectrometer.

[0071] Polymer cross-linking degree test method: Principle of cross-linking degree test: The trinitrobenzene sulfonic acid (TNBS) method is a method for determining the content of free amino groups in proteins. The TNBS method is based on the quantitative reaction of amino groups with TNBS. TNBS reacts with amino groups under weak alkaline conditions to form an intermediate complex with a chromophore. The intermediate complex has maximum absorption values ​​near 355 nm and 420 nm.

[0072] Test steps: 1) Take 20 mg of polymer, add 5 ml of 0.1 M sodium bicarbonate solution, pH 8.5, and then add 5 ml of 0.5% TNBS solution by volume, and react at 40°C for 2 hours.

[0073] 2) After the reaction is completed, add 15 ml of 6M hydrochloric acid and incubate at 60°C for 1.5 hours.

[0074] 3) After the reaction is completed, wait for the reaction solution to cool to room temperature, then add 25 ml of deionized water and mix evenly.

[0075] 4) Take out 5 ml of the mixed solution into a test tube, add 10 ml of ether, shake evenly and let it stand, wait for the liquid to separate, and then take out the upper layer of ether. Then, add 10 ml of ether and repeat the above steps three times. After the ether in the reaction solution is completely volatilized, observe the absorbance of the reaction solution at a wavelength of 345 nm. And compare it with the uncrosslinked microcarrier.

[0076] The cross-linking degree calculation formula is: (AB) / A*100%; where: A: absorbance of uncross-linked injectable microspheres; B: absorbance of injectable microspheres.

[0077] Embodiment 2-4 The difference between it and Example 1 is that the concentrations of sodium hyaluronate, chitosan and collagen are different, and the conditions in the preparation process are also different; the specific proportions of Example 2, Example 3 and Example 4 can be seen in Table 1.

[0078] Table 1

[0079] The average particle size, protein content and degradation time of the injectable collagen microspheres of Example 1, Example 2, Example 3 and Example 4, as well as the surface charge density and cross-linking degree of the intermediate polymer are shown in Table 2.

[0080] Table 2

[0081] The above is only a specific implementation of the embodiment of the present application, but the protection scope of the embodiment of the present application is not limited thereto, and any changes or replacements within the technical scope disclosed in the embodiment of the present application should be included in the protection scope of the embodiment of the present application. Therefore, the protection scope of the embodiment of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing injectable collagen microspheres, characterized in that: The following steps are involved: S1: preparing a polymer, wherein the polymer comprises sodium hyaluronate and chitosan; S2: adding the polymer and the neutralization solution to the collagen solution to obtain a mixed solution; S3: heating and stirring the mixed solution to obtain injectable collagen microspheres; S4: Drying the injectable collagen microspheres.

2. The preparation method according to claim 1, characterized in that: The S1 includes: S11: preparing a first mixed solution, wherein the first mixed solution includes a sodium hyaluronate solution and a chitosan solution; S12: emulsifying the first mixed solution to obtain an emulsified solution; S13: solidifying the emulsified solution to form microcarriers; S14: treating the microcarriers to cause a cross-linking reaction to form a polymer; S15: washing and drying the polymer.

3. The preparation method according to claim 1, characterized in that: In S2: The collagen solution is obtained by dissolving collagen in a hydrochloric acid solution, the collagen concentration is 3 mg / ml-15 mg / ml, and the hydrochloric acid concentration in the hydrochloric acid solution is 0.01 mol / L.

4. The preparation method according to claim 1, characterized in that: In S2: The ionic strength of the neutralization solution is 0.03-0.1, and the neutralization solution comprises sodium hydroxide and sodium dihydrogen phosphate solution; The pH value of the mixed solution is 6-8.

5. The preparation method according to claim 1, characterized in that: The S3 includes: The temperature of the mixed solution is heated from 1°C~15°C to 15°C~30°C, the heating rate is 1°C / h~10°C / h, and the mixed solution is continuously stirred during the heating process, the stirring rate is 100rpm~500rpm, and the stirring time is 5h~16h.

6. The preparation method according to claim 2, characterized in that: The S11 includes: S111: dissolving sodium hyaluronate in a monovalent metal salt solution to obtain the sodium hyaluronate solution; S112: dissolving chitosan in a monovalent metal salt acetic acid solution to obtain the chitosan solution; S113: Mixing the sodium hyaluronate solution and the chitosan solution to obtain the first mixed solution.

7. The preparation method according to claim 2, characterized in that: The S12 includes: S121: adding the oil phase and the emulsifier into a container and mixing; S122: adding the first mixed solution into the container and stirring and emulsifying to obtain the emulsified solution.

8. The preparation method according to claim 2, characterized in that: The S13 includes: S131: adding a first hydrophilic organic solvent to the emulsified solution to solidify and form microcarriers; S132: leaching out the microcarriers.

9. The preparation method according to claim 2, characterized in that: The S14 includes: S141: adding a catalyst to the second hydrophilic organic solvent; S142: adding the microcarrier to the second hydrophilic organic solvent to perform a cross-linking reaction to generate the polymer.

10. The preparation method according to claim 2, characterized in that: The S15 includes: S151: washing the polymer using a third hydrophilic organic solvent; S152: Drying the washed polymer.

11. The preparation method according to claim 6, characterized in that: The concentration of the monovalent metal salt in the monovalent metal salt solution is 0.5-2 mol / L, and the mass percentage of acetic acid in the monovalent metal salt acetic acid solution is 0.5-3%; The concentration of the sodium hyaluronate solution is 0.5%-10%, and the concentration of the chitosan solution is 0.5%-10%.

12. The preparation method according to claim 11, characterized in that: The monovalent metal salt includes at least one of sodium chloride and potassium chloride.

13. The preparation method according to claim 7, characterized in that: The oil phase comprises at least one of liquid paraffin, mineral oil and vegetable oil; The emulsifier includes at least one of sorbitan monooleate polyoxyethylene ether and sorbitan oleate.

14. The preparation method according to claim 13, characterized in that: The mass ratio of the oil phase to the emulsifier is (35-45):1; the mass ratio of the oil phase to the first mixed solution is 1:(4-10); The stirring rate of the emulsification is 500 rpm to 2000 rpm, and the stirring time of the emulsification is 2 h to 8 h.

15. The preparation method according to any one of claims 8 to 10, characterized in that: The first hydrophilic organic solvent, the second hydrophilic organic solvent and the third hydrophilic organic solvent all include at least one of ethanol, acetone and dimethylformamide; The first hydrophilic organic solvent, the second hydrophilic organic solvent and the third hydrophilic organic solvent are all aqueous solutions with a concentration of 30% to 95%.

16. The preparation method according to claim 7 or 8, characterized in that: The volume ratio of the first hydrophilic organic solvent to the oil phase is (0.8-1.2):1; The addition rate of the first hydrophilic organic solvent is 10 ml / min to 100 ml / min, and stirring is performed continuously during the addition of the first hydrophilic organic solvent. The stirring rate is 100 rpm to 800 rpm, and the stirring time is 1 h to 15 h.

17. The preparation method according to claim 9, characterized in that: The catalyst includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysulfosuccinimide (NHS), and the concentration of the catalyst is 0.5‰~4‰.

18. The preparation method according to claim 9, characterized in that: The temperature of the cross-linking reaction is 10° C. to 50° C., and the time of the cross-linking reaction is 5 h to 24 h.

19. An injectable collagen microsphere, characterized in that: Prepared by the preparation method according to any one of claims 1 to 18.

20. The injectable collagen microspheres according to claim 19, characterized in that: It comprises collagen, sodium hyaluronate and chitosan, wherein the sodium hyaluronate and the chitosan are connected by amide bonds to form a polymer; The mass ratio of the collagen to the injectable collagen microspheres is 10-50%, and the ratio of the sodium hyaluronate to the chitosan is (1.5-2.5):

1.

21. The injectable collagen microspheres according to claim 20, characterized in that: The diameter of the injectable collagen microspheres is 10µm to 800µm, and the injectable collagen microspheres have a three-dimensional mesh structure.

22. Use of the injectable collagen microspheres according to claim 19 as an implant filler, characterized in that: It can promote the regeneration of collagen in human tissues.

Citation Information

Patent Citations

  • Injectable hyaluronic acid microsphere as well as preparation method and application thereof

    CN113663126A

Cited By

  • Sterile collagen microspheres for injection and method of preparation and use thereof

    CN122682098A